RUMSPIL VED YUPNOFLODEN: En eksperimentel metode på et antropologisk feltarbejde - Wassmann, Jürg (Tidsskriftet Antropologi, 1995)
Jiirg Wassmann: Space Games at the Yupno River. An Experimental Method in Anthropological Fieldwork The author uses an example from an interdisciplinary study among the Yupno in New Guinea to point to the relevance of experiments in anthropological research on cognition. It is argued that an experimental method makes it possible to get information on the explicit and conscious use of cultural knowledge individuals employ when they solve posed problems. The results from the space games made possible a more detailed and clear insight in, and description of, the arrangement and use of the three different systems for spatial description among the Yupno. A main point through the article is that the results from the experiments only make sense against the background of an extensive fieldwork which provides a insight into the ethnographical context necessary for the analysis.